National Geographic picture atlas of our universe - Gallant, Roy A. (Washington, D.C. : National Geographic Society, 1994)
Text, photographs, paintings, and maps explore the history of astronomy, the solar system, the universe, and new space discoveries.
Includes index.
Keywords: Astronomy -- Pictorial works; Astronomy -- Charts, diagrams, etc; Astronomy; Atlas